2010
DOI: 10.1017/s1368980010002223
|View full text |Cite
|
Sign up to set email alerts
|

Availability of data assessing the prevalence and trends of overweight and obesity among European adolescents

Abstract: Objective: To review recent data on objectively measured overweight/obesity in national representative samples of European adolescents (aged 10-18 years), as well as availability of studies assessing trends in overweight/obesity in this target group. Attention was paid to the ability of the data to describe the obesity epidemic, especially in sociodemographic subgroups. Design/setting/subjects: Data on prevalence and trends in overweight/obesity among adolescents in the twenty-seven European Community member s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 35 publications
3
34
0
2
Order By: Relevance
“…9 The results obtained in this study of anthropometric measurements of Polish 13-year-old boys and girls have confirmed the epidemiologic reports, which show increasing incidence of overweight and obesity among adolescents in Europe, including Poland. 10,11 In our studies on a population accounting to 1,738 individuals, the percentage of overweight adolescents equaled to 12.5%, and obese adolescents -11.2%. A higher percentage of Polish adolescents (13-15 years of age) with overweight (13.8%) and obesity (2.8%) was reported by Jodkowska et al 11 In our study, overweight and obesity occurred more frequently in girls (16.8% and 12.9%) than in boys (8.4% and 9.6%).…”
Section: Discussionmentioning
confidence: 64%
“…9 The results obtained in this study of anthropometric measurements of Polish 13-year-old boys and girls have confirmed the epidemiologic reports, which show increasing incidence of overweight and obesity among adolescents in Europe, including Poland. 10,11 In our studies on a population accounting to 1,738 individuals, the percentage of overweight adolescents equaled to 12.5%, and obese adolescents -11.2%. A higher percentage of Polish adolescents (13-15 years of age) with overweight (13.8%) and obesity (2.8%) was reported by Jodkowska et al 11 In our study, overweight and obesity occurred more frequently in girls (16.8% and 12.9%) than in boys (8.4% and 9.6%).…”
Section: Discussionmentioning
confidence: 64%
“…5,12 The final scoring system ( for each element of the scoring system, as proposed in other meta-analyses. Studies were classified into three quality groups and labeled A if they managed to obtain 8-12 points, B when 4-7 points were collected and C when they scored less than 4 points.…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%
“…4 With regard to Europe, according to recent data there is wide geographical variation across European countries of obesity and overweight rates among children and adolescents. 5 The over-time trend of the phenomenon is uneven, following an augmentative trend in some countries, while in others there is evidence that the rates have leveled off. 5,6 One of the first arrows in the quiver of health care providers and policy formations is appropriate research assessing the epidemiologic transitions of childhood overweight and obesity at both a national and an international level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in physical activity as well as eating practices are occurring in developed and developing countries affecting children and adolescents. In industrialized and developing countries, obesity has increased at a fast rate especially since the 1980s in all age groups (1)(2)(3)(4)(5)(6)(7) .…”
mentioning
confidence: 99%